Heat Shock Protein 90 and Role of Its Chemical Inhibitors in Treatment of Hematologic Malignancies - Haojian Zhang; Adam Li; Shaoguang Li; Ngoc Ho (MDPI AG, 2012)
Heat shock protein 90 (Hsp90) is a conserved and constitutively expressed molecular chaperone and it has been shown to stabilize oncoproteins and facilitate cancer development. Hsp90 has been considered as a therapeutic target for cancers and three classes of Hsp90 inhibitors have been developed: (1) benzoquinone ansamycin and its derivatives, (2) radicicol and its derivates, and (3) small synthetic inhibitors. The roles of these inhibitors in cancer treatment have been studied in laboratories and clinical trials, and some encouraging results have been obtained. Interestingly, targeting of Hsp90 has been shown to be effective in inhibition of cancer stem cells responsible for leukemia initiation and progression, providing a strategy for finding a cure. Because cancer stem cells are well defined in some human leukemias, we will focus on hematologic malignancies in this review.